2006
DOI: 10.1002/bdrb.20093
|View full text |Cite
|
Sign up to set email alerts
|

Developmental immunotoxicity investigations in the SD rat following pre- and post-natal exposure to cyclosporin

Abstract: These results demonstrate the importance of a post-treatment follow-up period in developmental immunotoxicity studies, in order to distinguish between the transient effects of immune modulation and the persistent consequences of developmental toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…On the other hand, to the authors' knowledge, thymectomy at birth in rats has not been reported to result in immune dysregulation. Although cyclosporine treatment of newborn rats starting on PND 4 did have effects on the immune system, autoantibodies were not produced (Barrow et al, 2006). Clearly, even species presumed to follow similar immune system development can have different responses to immunotoxicants.…”
Section: Impact On Interpreting Differential Findings Across Non-clinmentioning
confidence: 91%
See 2 more Smart Citations
“…On the other hand, to the authors' knowledge, thymectomy at birth in rats has not been reported to result in immune dysregulation. Although cyclosporine treatment of newborn rats starting on PND 4 did have effects on the immune system, autoantibodies were not produced (Barrow et al, 2006). Clearly, even species presumed to follow similar immune system development can have different responses to immunotoxicants.…”
Section: Impact On Interpreting Differential Findings Across Non-clinmentioning
confidence: 91%
“…However, in utero exposure led to much more persistent effects, with TDAR responses reduced in offspring at 13 weeks-of-age, whereas adult TDAR responses returned to normal levels by 13 weeks. It is important to note that others have not shown similar effects (Barrow et al, 2006) and immunotoxicity endpoints may be differentially affected. However, it is clear that in some instances toxicity to the developing immune system may take longer to reverse, and the specific window of exposure may be important.…”
Section: Review Articlementioning
confidence: 95%
See 1 more Smart Citation
“…In our study, we focused on the immune system in pregnant rats. The exposure to immunosuppressive treatment during pregnancy can cause immune depression and persistent impairment of the immune system of both mothers and offspring . In our experimental study, we assessed the impact of ‘safe’ and ‘contraindicated’ drugs in combinations (the ones most frequently used in therapy of human kidney recipients) on changes in the immune system of female Wistar rats after exposure during pregnancy.…”
Section: Introductionmentioning
confidence: 99%
“…Holsapple et al (2003Holsapple et al ( , 2005 proposed a protocol for assessing developmental immunotoxicity (DIT) to evaluate the effect of drugs or chemicals on the development of immunity in pups. Study models using several kinds of animals (mouse, rat, pig, and monkey) were suggested for assessing DIT (Holladay and Blaylock, 2002;Chapin, 2002;Rothkotter et al, 2002;Buse et al, 2003), and some DIT studies on drugs or chemicals have already been reported (Dietert et al, 2004;Hussain et al, 2005;Pillet et al, 2005, Barrow et al, 2006. Still, little information on developmental immunotoxicity is currently available, making it all the more important to continue studies on the alteration of the immune systems after pre-or post-natal exposure to xenobiotic agents.…”
Section: Introductionmentioning
confidence: 99%